2020
DOI: 10.1038/s41396-020-0620-8
|View full text |Cite
|
Sign up to set email alerts
|

Population genomics and evolution of a fungal pathogen after releasing exotic strains to control insect pests for 20 years

Abstract: Entomopathogenic fungi are one of the key regulators of insect populations in nature. Some species such as Beauveria bassiana with a wide host range have been developed as promising alternatives to chemical insecticides for the biocontrol of insect pests. However, the long-term persistence of the released strains, the effect on non-target hosts and local fungal populations remains elusive, but they are considerable concerns with respect to environmental safety. Here we report the temporal features of the Beauv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 57 publications
0
24
0
Order By: Relevance
“…Mei at el. [ 154 ] reported on the ecological and evolutionary scenario of the Beauveria population genomics over 20 years after releasing exotic strains to control pine caterpillar pests. They found that the population was largely clonal in nature and the released strains could persist in the field for a long time (20 years) but with low recovery rates.…”
Section: Genomic Advances In Ascomycotamentioning
confidence: 99%
See 1 more Smart Citation
“…Mei at el. [ 154 ] reported on the ecological and evolutionary scenario of the Beauveria population genomics over 20 years after releasing exotic strains to control pine caterpillar pests. They found that the population was largely clonal in nature and the released strains could persist in the field for a long time (20 years) but with low recovery rates.…”
Section: Genomic Advances In Ascomycotamentioning
confidence: 99%
“…With this study Mei at el. [ 154 ] paved the way for researches on population evolution of other species of entomopathogens, especially for biocontrol species with narrow host ranges.…”
Section: Genomic Advances In Ascomycotamentioning
confidence: 99%
“…It is therefore conceivable that the multiple species or strain spores of fungal parasites can land on individual insect hosts to theoretically trigger co-infections. In reality, however, the insect cadavers collected from the fields are always mycosed by a single species/strain of fungal parasites [ 7 , 8 ]. On the other hand, coenzootic or coepizootic fungal insect diseases have been frequently observed in the field, where the same or different species of insects were killed and mycosed by different strains or species of fungal parasites [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Field application and recovery studies revealed that the inundative application of mycoinsecticide agents such as B. bassiana did not displace local population. Instead, different genotypic strains coexist in the field by infection of different insects, and less than 3% of the insect cadavers were mycosed by the released strains [ 7 , 21 ]. These kinds of studies have not investigated the effect of biocontrol releases on other species of fungal parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to that in Beauveria species (25), it is easy to induce sexual fruiting bodies for C. militaris (20). Thus, the fruiting bodies of C. militaris were induced both on silk moth pupae and rice medium (see Fig.…”
Section: Resultsmentioning
confidence: 87%